2018
DOI: 10.1177/1934578x1801301109
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HIV-1 Activities and Chemical Constituents from Leaves and Twigs of Santisukia pagetii (Bignoniaceae)

Abstract: The first phytochemical investigation of the leaves and twigs of Santisukia pagetii (Bignoniaceae) using a bioassay-guided fractionation led to the isolation and identification of seventeen known compounds, including four triterpenoids, 3-O-acetylpomolic acid (1), ursolic acid (2), 3-O-acetylursolic acid (3) and siaresinolic acid (4), three iridoid glycosides, specioside (5), verminoside (6) and ambiguuside (7), three flavonoid glycosides, luteolin-7-O-neohesperidoside (8), apigenin-7-O-neohesperidoside (9) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The comparison of IC 50 values in the current study with previous studies showed that the IC 50 values of these anti-HIV-RT drugs against HIV-RT were within the ranges of previous results; 0.084–9.67 µM for NVP, 14–47 nM for EFV, and 15–22 nM for RPV [ 26 27 28 29 30 ]. As the IC 50 values of NVP, EFV, and RPV against FIV-RT were in comparable ranges to HIV-RT, indicating similar abilities of these drugs against both enzymes ( Table 1 and Supplementary Fig.…”
Section: Discussionsupporting
confidence: 86%
“…The comparison of IC 50 values in the current study with previous studies showed that the IC 50 values of these anti-HIV-RT drugs against HIV-RT were within the ranges of previous results; 0.084–9.67 µM for NVP, 14–47 nM for EFV, and 15–22 nM for RPV [ 26 27 28 29 30 ]. As the IC 50 values of NVP, EFV, and RPV against FIV-RT were in comparable ranges to HIV-RT, indicating similar abilities of these drugs against both enzymes ( Table 1 and Supplementary Fig.…”
Section: Discussionsupporting
confidence: 86%
“…The position of functional groups was also clarified by HBMC correlations (Figure 2). Thus, the structure of 11 was conclusively determined to be 5,7-dihydroxyisocoumarin (Figure 1), and it was named euonymusin C. Repeated column chromatography of n-BuOH soluble fractions led to the isolation of three new compounds, euonymusin A-D (1, 10, and 11); one new set of spectroscopic data that had not previously been reported (2); together with ten known compounds whose chemical structures were identified as those of known compounds by comparing their spectroscopic data with data reported in the literature, namely, quercetin-3-O-β-Dgalactopyranoside (3) [27], quercetin-3,7-di-O-β-D-glucopyranoside (4) [27], isorhamnetin-3,7-di-O-β-D-glucopyranoside (5) [28], quercetin-3-O-sambubioside (6) [29], isoquercetin (7) [30], quercetin-3,3 ′ -di-O-β-D-glucopyranoside (8) [31], liriodendrin (9) [32], caffeic acid trans-3-O-β-D-glucopyranoside (12) [33], methyl trans-3-O-(β-D-glucopyranosyl) caffeate (13) [34], and benzyl gentiobioside (14) [34] (Figure 1).…”
Section: Structural Determination Of Compoundsmentioning
confidence: 99%
“…An anti-HIV1-RT activity assay, anti-syncytium test and cytotoxic study were done as reported by Pompimon, W., et al [4,5] and Limjiasahapong, S., et al [6].…”
Section: Anti-hivs Assay and Cytotoxic Studymentioning
confidence: 99%